Outcomes in Primary Powered Endoscopic Dacryocystorhinostomy: Comparison between Experienced versus Less Experienced Surgeons. Issue 6 (November 2014) - Ali, Mohammad Javed; Psaltis, Alkis James; Murphy, Jae; Wormald, Peter John
Background: This study compares the anatomic and functional outcomes of primary powered endoscopic dacryocystorhinostomy (DCR) in surgeons of differing levels of experience. Methods: A retrospective interventional study was performed of all consecutive powered endoscopic DCRs performed at a tertiary institution over a period of 10 years from 2002 to 2012. All patients completed a minimum of 3 months follow-up after stent removal. Patient records were reviewed for demographic data, clinical and surgical profiles, adjunctive procedures, complications, and success rates at last follow-up. The level of surgeon's experience performing the DCR was also documented. Anatomic success was defined as patent ostium on irrigation and functional success as free flow of dye into ostium on functional endoscopic dye test and resolution of epiphora. Results: Among the 160 DCRs performed by the consultant, all except four underwent intubation; 54.4% (68/125) of these patients required adjunctive procedures. There were no major complications in this group and at a long-term mean follow-up of 14.2 months, the anatomic and functional success rates were 98.1 and 95.6%, respectively. Among the 100 DCRs performed by the fellows, all underwent intubation and 40.8% (29/71) of the patients required adjunctive procedures. The complications include three cases of ostium granulomas and two patients each with postoperative bleeding, stent prolapse, and turbinoseptal synechiae. At the mean follow-up of 10.9 months, the final anatomic success was achieved in 95% of the cases and functional success in 89% of the cases. Conclusion: Powered endoscopic dacryocystorhinostomy is an effective procedure and offers excellent results in the hands of experienced surgeons. A good transfer of knowledge and skills along with supervision when required ensures a good surgical success rate, even when the training fellows operate.